Arahan Pengembangan Desa-desa Potensial di Kecamatan Mepanga Menjadi Kawasan Perkotaan Baru Berdasarkan Ketersediaan Sarana dan Prasarana - Rahmi, Tata Aisyah; Najib, Muhammad; Awalia, Rezki; Rizkhi, R (Prodi PWK Universitas Tadulako, 2025)
The transmigration program in Meganga District, Parigi Moutong Regency, began in 1973 with the establishment of the UPT in Unit I Mepanga, which has developed into five definitive villages, namely Kotaraya Village, South Kotaraya, West Kotaraya, East Kotaraya, and Southeast Kotaraya. These villages have the potential to be developed into New Urban Areas (KPB) in accordance with Government Regulation No. 3 of 2014. This research aims to formulate directions for the development of potential villages in Mepanga District into New Urban Areas based on the availability of facilities and infrastructure. The research method uses a mixed approach with descriptive analysis, scalogram, and centrality index. The results of this study show that these potential villages have the availability of facilities and infrastructure that still need improvement to meet the standards set in the Village Minister Regulation Number 25 of 2016. Based on the analysis of the scalogram and centrality index, Kotaraya Village as the main service center (Hierarchy I), supported by South and West Kotaraya Villages as supporting villages (Hierarchy II), and East and Southeast Kotaraya Villages as development villages (Hierarchy III). The direction of the development of potential villages in Mepanga District includes the improvement and development of basic infrastructure, inter-village connectivity, and regional planning regulations, as well as collaboration between the government, the community, and stakeholders needed to realize this area as a new integrated and sustainable growth center.